Dynamic properties of 3D printed cement mortar based on Split Hopkinson Pressure Bar testing. (July 2022) - Mo, Yixin; Xing, Jianchun; Yue, Songlin; Zhang, Yamei; Zhou, Qizhen; Liu, Xiao
Abstract: Concrete produced by 3D printing has been widely studied, however, most studies focus on the static properties of 3D printed materials, but few on dynamic properties. In this study, the dynamic properties of 3D printed cement mortar were evaluated from the dynamic compressive strength, energy dissipation density, failure modes, fragment distribution, and fractal dimension. In the strain rate range of 70 s −1 -140 s −1, the anisotropy of dynamic compressive strength diminishes with increasing strain rate, but remains more significant than the anisotropy of static compressive strength. Acoustic indices were used to evaluate the anisotropy of the dynamic compressive strength of 3D printed cement mortar, revealing an exponential relationship between ultrasonic pulse velocity (UPV) and dynamic compressive strength. The energy dissipation density under the same strain rate varies in three key printing directions. Finally, the number of main cracks is different in three printing directions in the failure process under the same strain rate, which leads to different degrees of damage, and thus different fragment distributions and fractal dimensions therein.